Optimizing strength and ductility in FCC high-entropy alloys through synergistic dual-phase precipitation - Peng Cheng; Boqiong Li; Yuanyang Sun; Liuqing Yang; Ruizhen Xie; Yuhong Zhao (Journal of Materials Research and Technology)
This study introduces a dual-phase synergistic strengthening strategy for high-entropy alloys (HEAs), focusing on the design of Co–Cr–Fe–Ni–Ti HEAs incorporating nanoscale γ′ particles and lamellar η phases. By tailoring the alloy composition and aging conditions, the size and volume fraction of the precipitates were effectively optimized. The tested alloys, subjected to different cold rolling reductions, fully recrystallized after high-temperature annealing, exhibiting significant differences in grain size, twin density, and dislocation density. Aging treatment induced the precipitation of γ′ particles within the grains and η phases at the grain boundaries, with their respective volume fractions increasing as Ti content increased. The S–Ti0.15 alloy (with 3.61 at.% Ti, processed by 70 % cold rolling, recrystallization annealing, and 650 °C aging) achieved an outstanding balance of strength and ductility, with an ultimate tensile strength exceeding 1 GPa and an elongation of 45 %. In particular, precipitation strengthening accounted for more than 80 % of the total strength increase, whereas an excessive amount of η phase led to a reduction in ductility. This study provides an innovative approach for optimizing the comprehensive mechanical properties of HEAs through synergistic precipitate design, highlighting its significant potential for engineering applications.